Creating a blue ocean strategy for a biostimulants company - Segovia, Sara Cheyenne (Kansas State University, 2021)
There is an opportunity to develop a biostimulants product as a new line for a crop services company. The biostimulants market is very competitive and characterized by companies that seem to over-promise and under-deliver to their customers. Yet, the potential for biostimulants to improve producer profitability by reducing the amount of fertilizers and other plant nutrients they use is immense. Creative Dynamics is considering introducing a new line of biostimulants into the market with a focus on pursuing a Blue Ocean Strategy. The objective of this research is to develop the strategy for successfully executing this Blue Ocean Strategy and assess the economic performance resulting from the strategy compared to a traditional competitive strategy under alternative competition conditions. Creative Dynamics follows the Blue Ocean framework to understand the current market space today in order to develop a strategy for market entry. Major points of differentiation discovered by the Blue Ocean Strategy Canvas include Creative Dynamics price offerings and yield increase potential related to their plant biostimulants product concepts. The simulation suggests that by focusing on points of differentiation, such as price and yield increase potential, Creative Dynamics could successfully present its new biostimulants line as a Blue Ocean product despite the noise in the market. Through carefully orchestrated and managed strategic price structure, the company should be able to sustain its new competitiveness for a long time.
Keywords: Biostimulants; Agribusiness; Blue Ocean; Strategy